Oltre il pluralismo religioso. Il veganismo come convincimento di coscienza (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Il caso Casamitjana Costa v. The League Against Cruel Sports - 3. Il veganismo nella giurisprudenza italiana - 4. Pari dignità delle coscienze … - 5. (segue) e specificità del fenomeno confessionale - 6. Definire le convinzioni personali tra libertà del singolo e necessità di accertamento - 7. Spunti conclusivi.Beyond religious pluralism. Veganism as an expression of freedom of conscienceABSTRACT: A recent judgement of the Employment Tribunals and a following one of the Tribunal of Bologna recognized veganism as a belief worth of protection. The two judges went beyond the bounds of the religious sphere, exploring the horizon of cultural pluralism, which the Italian Republic, as a secular state, should guarantee. The sentences therefore represent a starting point for addressing the complex issue of the relationship between law and conscience, which recently acquired major importance. As a matter of fact, according to an authoritative doctrine, there is a tendency in all Western legal systems to leave moral or ethical matters to individual self-determination, in accordance with the personalist and pluralist principle. This contribution will then start from the examination of the sentences and then it will deal with some of the main problems concerning freedom of conscience and its protection.